2017
DOI: 10.1073/pnas.1703139114
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsism6A demethylase activity modulates viral infection of a plant virus and the m6A abundance in its genomic RNAs

Abstract: N-methyladenosine (mA) is an internal, reversible nucleotide modification that constitutes an important regulatory mechanism in RNA biology. Unlike mammals and yeast, no component of the mA cellular machinery has been described in plants at present. mA has been identified in the genomic RNAs of diverse mammalian viruses and, additionally, viral infection was found to be modulated by the abundance of mA in viral RNAs. Here we show that the protein atALKBH9B (At2g17970) is a demethylase that removes mA from sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
272
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(291 citation statements)
references
References 52 publications
(130 reference statements)
7
272
0
Order By: Relevance
“…The present results showing that UPF1 promotes TSWV infection in Arabidopsis contrast with previous reports suggesting that non‐sense‐mediated decay limits infection of RNA viruses. These conclusions are based on increased expression of a PVX transgene in a upf1 mutant, transient expression assays in N. benthamiana of PVX and TCV with a dominant‐negative version of UPF1 (Garcia et al ., ; May et al ., ), and a moderate increase in susceptibility to AMV in upf1‐5 mutant Arabidopsis (Martínez‐Pérez et al ., ). To confirm and extend the role of UPF1 in virus infections, Col‐0 and upf1‐5 mutant plant were infected with PlAMV‐GFP and TuMV‐GFP.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The present results showing that UPF1 promotes TSWV infection in Arabidopsis contrast with previous reports suggesting that non‐sense‐mediated decay limits infection of RNA viruses. These conclusions are based on increased expression of a PVX transgene in a upf1 mutant, transient expression assays in N. benthamiana of PVX and TCV with a dominant‐negative version of UPF1 (Garcia et al ., ; May et al ., ), and a moderate increase in susceptibility to AMV in upf1‐5 mutant Arabidopsis (Martínez‐Pérez et al ., ). To confirm and extend the role of UPF1 in virus infections, Col‐0 and upf1‐5 mutant plant were infected with PlAMV‐GFP and TuMV‐GFP.…”
Section: Resultsmentioning
confidence: 97%
“…Transient overexpression of a dominant negative mutant of the Arabidopsis UPF1 protein with potato virus X (PVX), pea enation mosaic virus 2 (PEMV‐2) and turnip crinkle virus (TCV) resulted in increased virus accumulation in N. benthamiana leaves (Garcia et al ., ; May et al ., ). Consistent with these results, upf1 mutant plants are more susceptible to alfalfa mosaic virus (AMV) (Martínez‐Pérez et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, not all RRACH motifs are associated with m6A modification, as the m6A level is much lower than the abundance of RRACH motifs, indicating that the molecular mechanism regulating m6A modification is not fully understood (Liu and Pan, ). The Arabidopsis thaliana proteins ALKBH9B and ALKBH10B function as m6A erasers (RNA demethylases) that oxidatively reverse m6A methylation from single‐stranded RNA molecules (Duan et al ., ; Martínez‐Pérez et al ., ). YTH domain proteins act as m6A readers.…”
Section: The Composition Of the M6a Regulatory Network: Writers Erasmentioning
confidence: 97%
“…Transcriptome‐wide profiling has revealed that m6A modification is also a dynamic process in Arabidopsis (Luo et al ., ). Several studies have confirmed that m6A can revert to adenosine through the action of the m6A RNA demethylases ALKBH9B and ALKBH10B (Duan et al ., ; Martínez‐Pérez et al ., ). AtALKBH9B localizes to cytoplasmic granules, which contain siRNA bodies and can be directed to P bodies.…”
Section: M6a Erasersmentioning
confidence: 97%
See 1 more Smart Citation